Pengaruh Media Pembelajaran Aplikasi Canva Terhadap Hasil Belajar Siswa pada Mata Pelajaran Teknologi Informasi dan Komunikasi di MTsN 3 Kuningan (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out the learning using the Canva application in the subject of Information and Communication Technology in grade VIII MTsN 3 Kuningan. This study is experimental research, with a classical experimental design Classical Experimental Design. The subjects of the study were 30 students in grade VIII of MTsN 3 Kuningan. Research data was taken by questionnaire and observation sheet. The validity and reliability of the questionnaire were tested using Corrected Item-Total Correlation. The normality test was used the Shapiro Wilk test because the samples studied were less than 50. The results showed that there was an influence of the canva application on the learning outcomes of grade VIII students of MTsN 3 Kuningan in the subject of Information and Communication Technology, as evidenced by the significance value of 0.032 for the learning outcome variable